Effect of early initiation of steroid-sparing drugs in patients with bullous pemphigoid - Fenne, Inger Johanne; Askildsen Oftebro, Guro; Vestergaard, Christian; Frølunde, Anne Sofie; Bech, Rikke (Frontiers in Immunology, 2023)
Introduction: Bullous pemphigoid (BP) can be treated using systemic and topical glucocorticoids and/or other immunomodulatory agents. However, the long-term use of systemic glucocorticoids causes severe adverse side effects. This study was aimed at investigating whether the early initiation of corticosteroid-sparing therapy (CST) in BP patients results in better outcomes than late or no CST. Method: We retrospectively identified all BP patients referred to the tertiary centre; of the Department of Dermatology and Venerology, Aarhus University Hospital, Denmark, from 2015 to 2021. Patients’ demographics, comorbidities, treatment, remission of BP, length of admission, relapse, and 1-year mortality were recorded. All patients who received CST were dichotomised into two groups: initiated with CST <28 days or >28 days. The groups were compared using t-tests. Additionally, all patients who received CST were compared with those who received systemic glucocorticoids alone. Our cohort was compared with that of a previous study (2006-2013) performed in our department. In 2015, we revised our BP treatment guidelines to include the early initiation of CST. Results: On comparing the group of patients initiated with CST <28 days versus >28 days, we found no significant differences in the complications or mortality between the groups (p=0.63 and p=0.79, respectively). The <28 days group had a lower rate of relapse (p<0.05). On comparing data from this study with those from the previous study, conducted before we revised our treatment guideline, we found a reduced initial dose of prednisolone and reduced admission time in this study. No significant differences were found between patients treated with CST and those treated with systemic glucocorticoids alone. Conclusion: The rate of complications and 1-year mortality did not differ significantly between the two subgroups in this study. The relapse rate was lower in the CST <28 days group than in CST >28 days group. The initial dose of prednisolone and admission time were reduced in this study compared with those in the previous study performed before the implementation of a local treatment guideline recommending the early initiation of CST.